2014
DOI: 10.1063/1.4882421
|View full text |Cite
|
Sign up to set email alerts
|

A random matrix approach to detect defects in a strongly scattering polycrystal: How the memory effect can help overcome multiple scattering

Abstract: Articles you may be interested inModel-based imaging of damage with Lamb waves via sparse reconstruction Experimental characterization of fatigue damage in a nickel-base superalloy using nonlinear ultrasonic waves

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
0
36
1
Order By: Relevance
“…Table II shows the MSF-DORT imaging process performance for the bulk defect detection compared to TFM imaging. This results are also better than those presented by Shahjahan [2] due to two improvements. The first one is the specific wavelet treatment.…”
Section: -3contrasting
confidence: 45%
See 2 more Smart Citations
“…Table II shows the MSF-DORT imaging process performance for the bulk defect detection compared to TFM imaging. This results are also better than those presented by Shahjahan [2] due to two improvements. The first one is the specific wavelet treatment.…”
Section: -3contrasting
confidence: 45%
“…Shahjahan et al [2,5] already demonstrated the possibility of using this process to the detection of a side drilled-hole deeply embedded in a strongly scattering polycrystalline medium. In the next part an application of the MSF-DORT imaging process to the detection of side drilled-holes in a nickel based alloy and another to the plane defect detection will be presented and compared to the Total Focusing Method (TFM).…”
Section: Dort Ethodmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a deterministic method based on the random matrix approach allowed successful imaging of a reflector located about three mean free paths away from an ultrasonic array [8]. This method relies on the ability to distinguish between simple and multiple scattering via a singular value decomposition of the time reversal operator (DORT).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the researchers also discussed the Facebook, Twitter and other companies is how to choose to use a private cloud infrastructure to build large data service, and by using MapReduce and Hadoop and other big data technologies and tools to achieve PB-level data processing. At the same time, many scientific computing scientific computing tasks associated with big data services, such as the "Human Genome Project" and "Looking beyond the planet Earth" and other ultra-large-scale data, is deployed on multiple platforms such as cloud platform to complete large, complex calculations and data processing tasks [1][2][3] In summary, the process of library management tools enabling mobile Internet platform read data is the introduction of mobile cloud computing, can make full use of parallel computing peripherals can achieve rapid retrieval and recommendation, it enables mobile Internet platform library management, artificial Books intelligent recommendation and other functions. For multiple cloud services deployed in large data service, reliability of cloud services combined sister program performance for large data service has a crucial impact.…”
Section: Introductionmentioning
confidence: 99%